Experimental Study of Deltamethrin-Induced Nephrotoxicity in the Rat Model - Eugene A. Chigrinski; Taras V. Gerunov; Liudmila K. Gerunova; Yuri N. Fedorov; Nikolai V. Shorin (International Journal of Biomedicine, 2018)
The purpose of this study was to determine the nephrotoxic effect of deltamethrin in experimental animals at a dose of 43.5mg/kg (1/2 LD50). Materials and Methods: For the experiment, 48 male Wistar rats with a body weight of 240±10g were divided into 4 groups of 12 animals each. Groups 1 and 3 were control groups, which were administered a physiological solution intragastrically. The animals in Groups 2 and 4 received a single dose (43.5mg/kg) of the synthetic pyrethroid deltamethrin, which corresponds to 1/2 LD50. Rats were withdrawn from the experiment in two stages: 1) rats in Groups 1 and 2 – one day after the deltamethrin administration; 2) rats in Groups 3 and 4 – 3 days after the deltamethrin administration. Biochemical and pathomorphological changes in the kidneys were evaluated. The evaluation criteria were the content of pyruvate, inorganic phosphate, and glutathione and the activity of glutathione peroxidase activity (GPx), glutathione reductase (GR) and glutathione-S-transferase (GST) in the kidneys. Histological preparations of kidney tissue were studied. Results: The single administration of a toxic dose of deltamethrin caused a decrease in body weight of rats, an increase in kidney weight, and the accumulation of pyruvate and inorganic phosphate in the kidneys. A decrease in the GSH content in the kidney was accompanied by an increase in the activity of GPx, GR and GST. One day after the experiment, in the convoluted tubules, epithelial cells with blurred contours of the boundaries were enlarged; and the granularity of the cytoplasm containing vacuoles was expressed. The nuclei of epithelial cells had different sizes; some of them were in a state of pycnosis. In the organ parenchyma, large and small blood vessels full of blood were visible. Three days after the intoxication, these symptoms became more pronounced. In the intertubular connective tissue, hemorrhages and leukocyte infiltrates were detected. Conclusion: The study confirms the nephrotoxic effect of a single toxic dose (43.5mg/kg [1/2LD50]) of deltamethrin. Pathomorphological changes in the kidneys are accompanied by the disturbances in energy metabolism and activation of the glutathione antioxidant system with the development of glutathione deficiency.